PERSPEKTIF KEUANGAN ISLAM MENGHADAPI KRISIS KEUANGAN GLOBAL: TINJAUAN KONSEPTUAL - Anjarsari, Novita (Jurnal Akuntansi AKUNESA, 2013)
The Islamic financial system is needed as a new alternative to deal with the global financial crisis that can bring contagion effects to other countries. The purpose of this study is to analyze causes of crisis that were dominated by interest and derivatives practices in banking. Islamic financial system introduces a risk-based profit-loss sharing that provide justice through financing model (mudaraba and musharaka) in the transaction. Keywords: Islamic financial system, interest, derivative, profit-loss sharing.